The Evaluation of Noise Pollution at Samen District in Mashhad, Khorasan Razavi Province, Iran using Geographic Information System - ASIYEH MOTEALLEMI (International Journal of Occupational Hygiene, 2017)
Samen district is located in the city of Mashhad, Khorasan Razavi Province, Iran and is most famous for housing the shrine of Imam Reza. Every year, 32 million pilgrims visit the Imam Reza shrine from inside and outside the country. The question of noise pollution in this district, has been neglected compared to other forms of pollution. We investigated noise pollution using Geographic Information System (GIS) in this district.  Equivalent sound level, sound pressure level, noise pollution level and traffic noise index, were measured in the summer and fall of 2016. The measurements were done using EPA guidelines and were analyzed. GIS was employed to prepare the zoning map of the measured equivalent sound level and maximum sound level. The values of equivalent sound level at all of the measured stations exceeded the noise pollution guidelines suggested by Iranian Environmental Protection Organization. The value of this parameter for 87.5% of stations was 75 dB in summer. The noise pollution level value in 78% stations was higher than 82 dB in summer, and the value of this parameter in fall for 75% stations was higher than 79 dB. This area is suffering from a high degree of noise pollution. Noise maps due to being able to detect peoples’ habits of moving around the different parts of the city and at different times could facilitate computer-assisted control of the urban traffic.